Sexual Violence Against Yazidi Women as a Crime Against Humanity - Safaa Mohammednoori Ali (QALAAI ZANIST JOURNAL, 2021)
Sexual Violence Crimes Are Flagrant Violation of Human Rights. After the ((ISIS)) Organization occupied large areas in Iraq, and the barbaric actions committed by the ((ISIS)) Organization in Iraq, it completely ignored all standards of human rights and human dignity. This Organization uses rape as a weapon in attacks that amount to crimes against humanity, and Yazidi women and girls are considered the most suffering from Sexual violence to which they were subjected by this Organization. It should be noted that the four Geneva Conventions of 1949 and their two Additional Protocols of 1977, did not ignore this type of crime, and the role of the International Criminal Court in this field cannot be overlooked, and this is what we have clarified in the framework of the research. It is well known that Sexual violence is an inhuman and brutal behavior, which has become in contemporary wars an effective means of war to humiliate the opponent and break this morale, especially since this behavior has very serious psychological, Social and health effects, and we reached several conclusions, including; The captivity of Yazidi Women by individuals of the ((Islamic State in Iraq and the levant)) called ((ISIS)) is the most heinous crime, and the extent of the danger of the ((Islamic State in Iraq and the levant)) called ((ISIS)) to the world. We have proposed that the case be referred as a crime against humanity by the Security Council to the International Criminal Court under Article (13) of the court’s statute. Who has the right to refer the case directly to the court under Chapter Seven of the United Nations Chapter. And we recommended that a special text be specialized in international humanitarian Law that criminalizes these acts and punishes the perpetrators with the most severe panalties.